Review Review: Stimulant Augmentation with Antidepressant in Elderly Patients with Major Depressive Disorder: Stimulant Augmentation with Antidepressant in Elderly Patients with Major Depressive Disorder (International Journal of Scientific Research and Management (IJSRM), 2021)
According to the Centers for Disease Control and Prevention (CDC), depression affects about 1%-5% of the general elderly population, 13.5% in elderly who require home healthcare, and 11.5% in older hospital patients” CDC, 2017. Depression in the elderly is accompanied by functional weakening and early death due to suicide and other causes, Symptoms may include sadness; lack of interest, power, and ability to concentrate; insomnia and decreased appetite; and co-disease. Elderly patients have a lower response to antidepressant medications than adult patients.